Gratitude as a Contributing Factor to Mental Health in Addolescents - Muh. Setiawan Sahib (unprimdn.ac.id, 2025)
This integrative review synthesizes findings from ten empirical studies published between 2015 and 2025 that examine the role of gratitude as a protective factor for adolescents’ mental health. Using thematic analysis supported by a structured coding manual and thematic mapping, the review identifies consistent evidence that gratitude reduces stress, anxiety, and depression while enhancing life satisfaction, resilience, and psychological well-being. These cross-cultural findings extend the Broaden-and-Build Theory within collectivist contexts and highlight gratitude as an adaptive emotional resource that strengthens social connectedness and positive psychological functioning. Practically, gratitude-based interventions such as gratitude journaling and structured reflective practices offer a simple, low-cost, and effective preventive strategy to support youth mental health within educational settings.